University Selectivity and the Graduate Wage Premium: Evidence from the UK - Ian Walker; Yu Zhu (Institute of Labor Economics (IZA), 2017)
We study the relative labour market wage outcomes of university graduates in the UK using the Labour Force Survey (LFS), matched to mean standardised admission scores at the institution*subject*cohort level using data on high school achievement scores of students admitted to these courses. Unlike earlier UK studies, we are able to consider the effect of differences in undergraduate degree subjects, degree class, and in particular the selectivity of the subject at the Higher Education Institution (HEI) attended. Our results show that selectivity of undergraduate degree programmes plays an important role in explaining the variation in the graduate wage premium across HEIs and subjects. In fact, much of the observed differential in relative wage outcomes across institutions*subjects is due to the quality of students that HEIs select.
Keywords: I23; I26; 330; college selectivity; graduate wage premium